The sources and influencing factors of dissolved organic carbon under high-sediment environments – A case from Wuding River Basin - Xia, Manhong; Xue, Nan; Hu, Bo; Gong, Xinru; Wang, Zhoufeng; Zhao, Xiaohong (Frontiers in Environmental Science, 2025)
River sediments are important carbon reservoirs in terrestrial–aquatic systems, and a thorough understanding of the factors that influence the sources and distribution of organic carbon in river sediments can help us understand the carbon cycling process in river ecosystems. In this study, 21 river sediment samples were collected along the upstream–downstream gradient of the Wuding River Basin. The study revealed that (1) the sources of DOC in the Wuding River Basin were spatially heterogeneous, with plankton being the largest source of DOC upstream (39%), whereas terrestrial sources were the largest source of DOC downstream (54%). (2) Influenced by geomorphic conditions and land use, the gradually increasing hydrodynamic conditions from upstream to downstream prompted the migration of surface soil organic matter and nutrients such as effective nitrogen (AN), total phosphorus (TP), and total nitrogen (TN) to the river channel, resulting in an increase in the concentration of suspended sediment, which led to the accumulation of organic carbon in the downstream section of the river. (3) Using macrogenomic techniques, microbial - driven carbon cycling processes were identified and predicted. Downstream has greater carbon - cycling potential than upstream. Upstream DOC is positively correlated with anaerobic carbon fixation and methanogenesis (p < 0.001). Downstream DOC is negatively correlated with the rTCA cycle (p < 0.001), inhibiting autotrophic fixation as microbes use available carbon. The results of this study provide data to support ecological restoration, carbon sink enhancement, and water quality assurance in high-sediment rivers.